Measurement of total liver blood flow in intact anesthetized rats using ultrasound imaging. Issue 2 (4th March 2021) - Gibson, Christopher R.; Gleason, Alexa; Messina, Eric
Abstract: This short report describes the measurement of total liver blood flow in commonly used laboratory rats using the relatively non‐invasive approach of ultrasound imaging. A total of 29 rats ( n  = 26 Wistar‐Han, n  = 3 Sprague–Dawley) were imaged and both male and female rats were included. The mean (SD) total liver blood flow of all animals combined was 33.3 ± 7.8 mL/min, or 104.3 ± 17.1 mL/min/kg when normalized to observed body weight at the time of imaging. There was a trend for higher unnormalized total liver blood flow as body weight increased and the female rats had, in general, the lowest body weight and total liver blood flow of the animals studied. There were no major differences in total liver blood flow between the small number of Sprague–Dawley rats used in the study and the larger Wistar‐Han group. Further research would be needed to accurately characterize any subtle differences in body weight between rats of different strains, sexes, and body weight. Abstract : Mean (SD) total liver blood flow as measured by ultrasound imaging in female and male rats separately and combined (Panel A). The mean total liver blood flow for both sexes combined was 33.3 (7.8) mL/min. Mean (SD) body weight‐normalized total liver blood flow as measured by ultrasound imaging in female and male rats separately and combined (Panel B). The mean body weightnormalized total liver blood flow for both sexes combined was 104.3 (17.1) mL/min/kg.